Childhood in Calgary’s Postwar Suburbs: Kids, Bullets, and Boom, 1950–1965 - Onusko, James (Urban History Review / Revue d'histoire urbaine)

(untitled) (Urban History Review / Revue d'histoire urbaine, 2015)
Suburban living has become the definitive housing choice for a large majority of North Americans since the end of the Second World War. A longstanding image of the postwar suburbs highlights a stable and undifferentiated experience for young Canadians. Much of the popular and scholarly literature on these spaces tends to portray them as exclusively middle class, homogeneous, conformist, conservative, and alienating. While Canadian suburbia has appeared similar in outward appearance, increasingly more so in the postwar era, this has not necessarily meant that the suburbs have created total homogenization in the built environment, lifestyles, attitudes, and values of their inhabitants. Suburbs embody substantial economic, political, and cultural power in North America. In the past two decades a more nuanced response from academics on suburbia has emerged, in that some diversity, on several levels, is now noted. This article builds on this alternate view. I argue that young suburbanites were exposed to aggressive imagery, discursive constructs, and everyday practices in an attempt to discipline them for possible military service, ongoing participation in civilian defence, and that they internalized much of this. The resulting general atmosphere prepared them to engage “enemies,” under the auspices of the Cold War that lay both within, and outside, postwar childhood spaces. Evidence is based on oral histories, images produced for children, newspaper editorials, and the school-based literature and art that suburban students created.